Mewujudkan Pemerataan Pendidikan: CLC di Perbatasan Indonesia-Malaysia (Global Focus, 2022)
The complexity of border studies is a reflection of the socio-political realities that exist in border areas. Most of the time border areas are synonymous with conflict and militarization. But at the same time, cooperation between various international actors in the border area is also taking place. One example is the collaboration between three actors (Government of Indonesia, Government of Malaysia, and Palm Oil Plantation Company) in the Indonesia-Malaysia border area in North Kalimantan Province-Sabah State to establish and run a Community Learning Center (CLC) program as an effort to overcome limitations of access to education for children of Indonesian migrant workers in palm oil plantations in Sabah. The existence of a Community Learning Center (CLC) is a form of alignment of interests between actors in the case of fulfilling the right to education for the children of Indonesian migrant workers in the State of Sabah. CLC as a form of cross-border cooperation is possible when the interests of the Government of Indonesia, the Government of Malaysia and palm oil plantation companies in the State of Sabah are aligned. The interest of the Indonesian government is to provide access to education for Indonesian citizens (WNI) residing in the State of Sabah, Malaysia. The interest of the Malaysian government is to maintain sovereignty within the regulatory authorities within its territory, in this case concerning population administration, While palm oil companies interest is to maintain its business sustainability by abiding to the rules of both countries.